The emission benefits of European integration - Luís Costa; Vincent Moreau (Environmental Research Letters, 2019)
Simulating the implications of Brexit on the UK’s emissions embodied in trade with a multi-region input–output table exposes the benefits of European integration. Under 2014 trade volumes, technologies and energy mixes, a hard Brexit—reverting to a trade pattern between the UK and the EU prior to the European Internal Market (EIM)—would imply a rise of about 0.215Gt of CO _2 eq in the UK’s emissions embodied in imports. This is equivalent to a 38% rise in UK’s imported emissions in 2014 and roughly equal to the territorial emissions of the Netherlands in 2017. Substituting imports from the EU with those from the Rest of the World (RoW), under the same conditions, implies adding 0.35 kg of CO _2 eq, on average, to each dollar of activity imported in the UK. This underlines the emission benefits of an integrated European market abiding to common environmental standards and climate policies. Filling the gap in imports lost from the UK to the EU by stepping up production within the EIM would result in an extra 0.012Gt of CO _2 eq, a rather small increase when compared to the additional emissions in the UK’s imports following Brexit. Should the EU reallocate the lost imports from the UK to the RoW, a total of 0.128Gt of CO _2 eq would be added to the EIM imports. This exposes the environmental benefits in terms of emissions in keeping UK trade closely linked to the EU and the important role that Single Member States can play indirectly on EU’s import emissions. In terms of emissions embodied in trade, the sum of the EU market is, paradoxically and for the better, less than the sum of its individual parts.